Structural characterisation of a uracil containing hairpin DNA by NMR and molecular dynamics. - Ghosh, M (1999)
Three-dimensional (3D) structure of a hairpin DNA d-CTAGAGGATCCTTTUGGATCCT (22mer; abbreviated as U4-hairpin), which has a uracil nucleotide unit at the fourth position from the 5' end of the tetra-loop has been solved by NMR spectroscopy. The(1)H resonances of this hairpin have been assigned almost completely. NMR restrained molecular dynamics and energy minimisation procedures have been used to describe the 3D structure of the U4 hairpin. This study establishes that the stem of the hairpin adopts a right handed B-DNA conformation while the T(12)and U(15)nucleotide stack upon 3' and 5' ends of the stem, respectively. Further, T(14)stacks upon both T(12)and U(15)while T(13)partially stacks upon T(14). Very weak stacking interaction is observed between T(13)and T(12). All the individual nucleotide bases adopt ' anti ' conformation with respect to their sugar moiety. The turning phosphate in the loop is located between T(13)and T(14). The stereochemistry of U(15)mimics the situation where uracil would stack in a B-DNA conformation. This could be the reason as to why the U4-hairpin is found to be the best substrate for its interaction with uracil DNA glycosylase (UDG) compared to the other substrates in which the uracil is at the first, second and third positions of the tetra-loop from its 5' end, as reported previously.